2021
DOI: 10.1016/j.pathol.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observations in perfusion-fixed human non-alcoholic fatty liver disease biopsies

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a widespread liver disease in Western society, but its multifactorial pathogenesis is not yet fully understood. Ultrastructural analysis of liver sinusoidal endothelial cells (LSECs) in animal models and in vitro studies shows defenestration early in the course of NAFLD, promoting steatosis. LSECs and fenestrae are important in the transport of lipids across the sinusoids. However, human ultrastructural data, especially on LSECs and fenestrae, are scarce. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…At physiological perfusion pressures, sinusoidal fenestrae act as a mechanical sieve to macromolecules and cellular projections that may come into contact with the microvilli of hepatocytes across the space of Disse. As recently reported, loss of fenestration in LSECs is more commonly seen in isolated steatosis compared to steatohepatitis [33]. These surprising observations suggest that in some situations loss of fenestration could be a protective mechanism intended to prevent exposure of hepatocytes to excess large molecules of lipids or albumin-bound small molecules such as toxic substances or microbial metabolites received through the portal circulation [33].…”
Section: What Cellular and Molecular Mechanisms Are Associated With Subclinical Portal Hypertension In Nafld?mentioning
confidence: 71%
“…At physiological perfusion pressures, sinusoidal fenestrae act as a mechanical sieve to macromolecules and cellular projections that may come into contact with the microvilli of hepatocytes across the space of Disse. As recently reported, loss of fenestration in LSECs is more commonly seen in isolated steatosis compared to steatohepatitis [33]. These surprising observations suggest that in some situations loss of fenestration could be a protective mechanism intended to prevent exposure of hepatocytes to excess large molecules of lipids or albumin-bound small molecules such as toxic substances or microbial metabolites received through the portal circulation [33].…”
Section: What Cellular and Molecular Mechanisms Are Associated With Subclinical Portal Hypertension In Nafld?mentioning
confidence: 71%
“…Naturally, this indicates defenestration that was apparently present in these livers. Importantly, fenestrae were again present in NASH livers (Verhaegh et al 2021) (Fig. 6a, b).…”
Section: Endothelial Fenestrae and Fatmentioning
confidence: 85%
“…Reported defenestration in steatotic livers results in the creation of capillaries with more or less continuous endothelium (DeLeve 2015;Horn et al 1987;Schaffner et al 1963a). Importantly, defenestration occurs in early phases in NAFLD patients (Verhaegh et al 2021). However, according to our present observations, fenestrae return in NASH (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NASH patients, much more than NAFLD ones, showed higher mitochondrial diameters, intra-mitochondria crystalline inclusions and granules in the matrix which correlated with both mitochondrial swelling and OXPHOS failure [85]. Recently, Verhaegh et al have observed ultrastructural changes by using transmission electron microscopy in 37 NAFLD patients, of whom 12 had NASH [88]. In this study, the presence of giant mitochondria showed no differences between patients with or without NASH, according to the results of Ahishali et al [87], supporting that the appearance of megamitochondria could represent a transitory phase between simple steatosis and NASH.…”
Section: Megamitochondria and Mitophagy: The Impact Of Morphological mentioning
confidence: 99%